Environmental Impact Assessment of Biomass Co-Firing and Particulate Filtration Stability in a Remote-Area Stoker Coal Power Plant - Anton Tonapa; Widayat Widayat; Silviana Silviana (BIORE Scientia Publisher, 2026)
High-ratio biomass co-firing has emerged as a practical pathway for reducing emissions from small coal-fired power plants in remote island grids. This study evaluates the environmental performance of palm kernel shell (PKS) co-firing at 50%, 75%, and 100% blending ratios in a stoker-fired boiler at PLTU Tidore, Indonesia. Direct stack measurements and fuel characterization were used to quantify the effects of PKS substitution on sulfur dioxide (SO₂), nitrogen oxides (NOx), particulate visibility, and ash characteristics, while also assessing the stabilizing role of a redundant baghouse filtration configuration. The strongly reduced sulfur and ash content of PKS, as detailed in the fuel analyses, led to substantial declines in SO₂ emissions. Concentrations decreased from 182.95 mg/Nm³ under coal-only operation to 16.53 mg/Nm³ during 100% PKS firing. NOx levels remained within an operationally stable range (303.87–452.14 mg/Nm³) despite non-linear fluctuations associated with fuel–temperature interactions. PKS firing also resulted in progressively lighter stack plumes and the production of finer, less clinker-forming ash. Throughout all tests, the redundant bag filter system maintained uninterrupted particulate control and prevented opacity excursions, ensuring the reliability of the environmental measurements. These results demonstrate that PKS co-firing, supported by robust filtration redundancy, provides a feasible and cost-effective approach for improving air quality performance in isolated coal-dominated grids. The findings highlight a replicable strategy for integrating biomass into small-scale thermal plants while maintaining emission stability and operational continuity.